A middle - late Eocene neoselachian assemblage from nearshore marine deposits, Mahajanga Basin, northwestern Madagascar. - Karen E Samonds; Tsiory H Andrianavalona; Lane A Wallett; Iyad S Zalmout; David J Ward (PLoS ONE, 2019)
We report here the first neoselachian fossil fauna from Eocene nearshore marine deposits of the Mahajanga Basin, northwestern Madagascar. The fauna includes seven species of shark: Nebrius blankenhorni, Brachycarcharias koerti, Galeocerdo eaglesomei, two species of Carcharhinus (one of which is described as a new species), Physogaleus, Rhizoprionodon and Sphyrna. Three species of rays were also recovered: Pristis, Myliobatis and an undetermined dasyatid ray. This fauna represents the first Cenozoic neoselachian fossil record from the Eocene of Madagascar and broadens our understanding of their evolutionary and biogeographic history in the southern hemisphere during this time. Although the diversity of the genera and species of the fauna is very low, the age and similarity of genera to those in Congo, west Africa, Arabia, Asia, Europe, and North, Central, and South America suggests that these genera were broadly distributed and diverse within the shallow marine settings of the Tethyan and southern provinces during middle and late Eocene.